Udział wiernych we Mszy św. sprawowanej przez kapłanów Bractwa Kapłańskiego Świętego Piusa X (FSSPX) w świetle aktualnych wytycznych Stolicy Apostolskiej - Pietras, Dawid (Poznańskie Studia Teologiczne, 2022)
The Society of Saint Pius X (SSPX) is a community of the Catholic Church suspended in 1975. The priests of the community are not incardinated and do not perform priestly ministry iuxta legem in the Church. Moreover, when they are ordained without the required dimissories, they are completely suspended. Despite this canonical irregularity, SSPX priests celebrate Masses validly. In addition, by the decision of Pope Francis they have validly and licitly administered the Sacrament of Penance since 2015. They can also celebrate Mass on the occasion of marriage. Apart from these situations, the Apostolic See cannot recommend attending SSPX Masses because of the lack of the full ecclesial communion in this Society. In the opinion of most canonists, despite the canonical irregularity of the priests of the Fraternity, it is possible to formally fulfill the duty of attending Mass on the feast of obligation.